Multilevel Analysis on Factors Associated with Occurrence Chronic Energy Deficiency among Pregnant Women - Rachmawati, Nur Cahya; Dewi, Yulia Lanti Retno; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2019)
Background: One of the nutritional problems experienced by pregnant women is chronic energy deficiency (CED). Chronic energy deficiency is a condition in which women of childbearing age